The factors which affect the effectiveness of job rotation in Felda Plantations Sdn Bhd / Noorshazreena Mohmd Razi - Mohmd Razi, Noorshazreena (Faculty of Business and Management, 2010)
Some firms have been pursuing a practice called job rotation, which assigns each worker not to a single and specific task but to a set of several tasks among which he or she rotates with some frequency. However, the difficulties of changing the organizational structure of an entire facility can prove difficult. Due to this problem, organization must identify the factors which contribute to the job rotation effectiveness. There are three main factors including employee’s readiness, management support and task orientation in order to determine the factors which affect the effectiveness of job rotation among 50 employees in Felda Plantations Sdn Bhd. Results of the present study showed that the most influential factors that affects job rotation effectiveness in FPSB is employee’s readiness. It’s also shows that employee’s readiness has a positive correlation relationship with job rotation effectiveness in FPSB. At the end of this study, the researcher come out with several recommendations in order to give clear vision for the organization to increase the effectiveness of job rotation and will give positive impacts towards employees and organization.